Peningkatan akumulasi tiamin pada kultur Escherichia coli melalui peningkatan oksigenasi dan penghilangan rpoS - Nuraliah Rusman; Prayoga Suryadarma; Nisa Rachmania Mubarik (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Microorganisms as cell factories in producing a product are strongly influenced by their metabolism. engineering microbial metabolism by increasing coenzymes that play a role in enzyme activity. Thiamine diphosphate is one of the coenzymes that are commonly found in the metabolic pathways of microbial cells. Increasing the thiamine formation pathway as a precursor in the thiamine metabolic pathway is a strategy in this study. Enhancing thiamine accumulation in Escherichia coli culture by inducing oxygenation level and deleting rpoS was investigated. The investigation was conducted by comparing the cultivation of Escherichia coli BW25113 (parent strain) and BW25113-∆rpoS (rpoS mutant) cultures under aerobic conditions at different shaking rotation rates of 150 and 200 rpm. The measured parameters were thiamine accumulation, dry cell weight, acetate concentration and glucose consumption of the cultures. Inducing oxygenation level of parent strain cultures through increasing shaking rotation rate from 150 to 200 rpm induced 40 % thiamine accumulation. Meanwhile, deletion of rpoS increased 9,5 % thiamine accumulation compared to parent strain culture